Definiowanie pojęcia „zawód zaufania publicznego”: [Defining term of „the profession of public trust”] (Studia Prawnicze / The Legal Studies, 2012)
Nie ma zapewne obecnie zawodów, których wykonywanie pozostawałoby poza zainteresowaniem prawa, są jednak też takie, których wykonywanie odgrywa szczególną rolę w społeczeństwie. Do nich należą „zawody zaufania publicznego” obejmujące grupę osób wykonujących czynności, które wymagają wysokich kwalifikacji, odbycia odpowiedniej praktyki oraz pozostawienia im samodzielności w wykonywaniu zawodu.Pojęciem „zawód zaufania publicznego” posługuje się Konstytucja RP z 1997 r., która w art. 17 ust. 1 wyodrębnia „samorząd zawodowy zawodów zaufania publicznego”, natomiast w ust. 2 tego przepisu stanowi „o innych rodzajach samorządu”.Przepisy ustawy zasadniczej ani innych ustaw nie definiują jednak tego rodzaju zawodów, nie wskazują też katalogu zawodów, które można byłoby uznać za „zawody zaufania publicznego”, pozostawiając powyższe kwestie uznaniu ustawodawcy, co stwarza liczne problemy praktyczne. The legislature introduced a new category in the Polish law with the provisions of the Constitution. This category is „the profession of public trust”, which is currently an important element of the professional body characteristic. The provisions of the Basic law or other laws do not define this type of event, they do not indicate a list of professions that could be considered as „the professions of public trust”, leaving these issues to the legislature’s recognition, creates a number of practical problems. The attempt to define „the professions of public trust” is undertaken by doctrine and case law, which leads to formation of various structures of this definition, as well as determine various characteristics of people who perform such profession. In general, it is assumed that definition of the profession should respond both social idea and needs to be worked out in accordance with the definition, indicating that individuals who practice profession of public trust entrust with information about the private life of people who are provided by their services. This information, that are essential issues of the individual, determine its social status, are also professional secrecy of the person providing services. In particular, such profession is to handling personal or business needs, and can be performed only by persons permitted to practice this profesion after checking the necessary knowledge and skills. The Constitutional wording “professionals of public trust” indicate also an individual providing the profession by the public trust by a person. It is not therefore possible to pursue the profession of public trust neither by a legal person or an organizational unit without a legal personality. Individuals performing that professions are entrusted with public functions, who are associated with public powers. Therefore, to give some professions a character of the profession of public trust, within the meaning of the Constitution, is the statutory imposition of certain restrictions in the scope of the constitutional freedom of access to the profession and for its providing, and the inclusion of persons providing such professions obligation membership of professional body. Imposition of certain restrictions is not for creating a specific group of professional privilege, but serving the public interest, and the scope of the restrictions should be adequate to protect that interest. An attempt to build a normative definition of „the profession of public trust” has been also taken by the government in the draft law of the professional body custody of the proper providing the professions of public trust and supervision of the activities of professional bodies. The draft met with sharp criticism and as a result that has not been adopted. As a consequence of above, in spite of the rich literature and case law, it is difficult to clearly define the term „profession of public trust”. It has been unable to work out a compromise as the catalog of the characteristics of group of professions, even though some of its attributes are repeated by authors expressing their opinion on this subject, as well as the case law of the Constitutional Tribunal. However semantic range of the term is particularly important because allocating a specific profession in the group is related to the legal consequences by granting specific rights and obligations of parties executing „profession of public trust”. There is a need, again, to take an effort in the performance of legal concepts of „the professions of public trust” for which professional bodies are established in Article 17 of the Constitution. Certainly, this is a contest in which the general well-being and social welfare are entrusted to the professional group, and therefore they require a high level of ethics. Moreover, the relations between the persons performing the profession and their customers are characterized by a relationship of trust, certified by the criminal law, and by certain privileges in administrative proceedings. People performing such professions come under specific codes of deontological ethics. They act in the public interest and to protect certain public goods.